Copper wire sheath material and preparation method thereof

A copper wire sheath material combining polypropylene, ethylene acrylate rubber, and a multi-effect flame retardant addresses the flammability and mechanical strength issues of polypropylene, providing enhanced stability and safety for cables.

CN119220020APending Publication Date: 2024-12-31ANHUI YINGSHUO ELECTRONIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411519162.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing copper wire sheath materials, primarily made of polypropylene, suffer from flammability, poor antioxidant properties, and reduced mechanical strength over time, failing to meet the higher performance demands in cable technology.

Method used

A copper wire sheath material is prepared by mixing polypropylene resin with ethylene acrylate rubber, modified glass fiber, and a multi-effect flame retardant, which includes Si-N flame retardant components, sulfur elements, semi-hindered phenol structures, and carbon-carbon double bonds, enhancing mechanical strength, flame retardancy, and aging resistance.

Benefits of technology

The sheath material exhibits improved mechanical strength, stable flame retardancy, and enhanced aging resistance, ensuring long-lasting performance and safety in cable applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107558800000031
    Figure BDA0005107558800000031
  • Figure BDA0005107558800000041
    Figure BDA0005107558800000041
  • Figure BDA0005107558800000042
    Figure BDA0005107558800000042
Patent Text Reader

Abstract

The invention discloses a copper wire sheath material and a preparation method thereof, and belongs to the technical field of cable materials. Comprising the following raw materials in parts by weight: 80-100 parts of polypropylene resin, 20-30 parts of ethylene acrylate rubber, 5-15 parts of a multi-effect flame retardant, 10-20 parts of modified glass fibers, 0.1-0.3 part of an initiator and 2-4 parts of a lubricant. The prepared sheath material takes polypropylene as a matrix, and ethylene acrylate rubber is added, so that the aging resistance of the sheath material can be enhanced to a certain extent; wherein the modified glass fiber has good compatibility with a matrix, and can enhance the mechanical strength of the sheath material; wherein the multi-effect flame retardant can significantly enhance the flame retardant property, aging resistance and certain mechanical properties of the sheath material, and the properties are long-lasting and stable; therefore, the prepared sheath material is excellent in mechanical strength, has stable and efficient flame retardance and aging resistance, and has important application value in the technical field of cable materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and in particular relates to a copper wire electric wire sheath material and a preparation method thereof. Background Art

[0002] Wires are carriers for transmitting electrical signals and electric currents. The stability of their power supply will directly determine the operating safety of the equipment. At the same time, with the development of electric energy, the application of electrical equipment is becoming more and more popular, and the performance requirements for wires are also getting higher and higher. The composition of wires can be generally divided into three main structural components: conductor, insulation layer and sheath.

[0003] Copper wire has extremely high conductivity, second only to silver, and is an ideal material for the manufacture of wires and cables. This enables copper wires to effectively transmit electrical energy and reduce energy loss. In addition, copper wires have high thermal conductivity, can quickly dissipate heat, reduce the possibility of overheating of wires, and ensure the safety of wires. Due to their excellent performance, they are often used as conductor materials for wires. In order to protect the copper wire, an insulating layer and a sheath layer are usually coated on the surface of the copper wire. Since the outermost layer of the wire is the sheath layer, which is directly in contact with the external environment, the performance of the sheath determines whether the performance of the cable is excellent. Common cable sheath materials include polypropylene, polyethylene, cross-linked polyethylene, polyvinyl chloride, etc. Among them, polypropylene is referred to as PP, which is a polymer formed by polyaddition reaction of propylene. It is a thermoplastic synthetic resin with excellent performance, chemical resistance, heat resistance, electrical insulation, high-strength mechanical properties and good high wear-resistant processing performance, etc. However, polypropylene has a low oxygen index and is a flammable material, which has certain safety hazards. In addition, polypropylene has poor antioxidant properties. After long-term use, the mechanical strength decreases significantly. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of cable material technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a copper wire electric wire sheath material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing a copper wire sheath material comprises the following steps:

[0007] The polypropylene resin is placed in a vacuum oven and dried at 100°C for 12 hours. The fully dried polypropylene resin, ethylene acrylate rubber (AEM), multi-effect flame retardant, modified glass fiber, initiator and lubricant are put into a mixer and mixed for 30 minutes. The mixture is then added into a twin-screw extruder for melt blending and extrusion to obtain a copper wire sheath material.

[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of polypropylene resin, 20-30 parts of ethylene acrylate rubber, 5-15 parts of multi-effect flame retardant, 10-20 parts of modified glass fiber, 0.1-0.3 parts of initiator, and 2-4 parts of lubricant.

[0009] Furthermore, the initiator is one of benzoyl peroxide, dicumyl peroxide, and tert-butyl perbenzoate.

[0010] Furthermore, the lubricant is one of paraffin, zinc stearate, magnesium stearate and epoxidized soybean oil.

[0011] The prepared copper wire sheath material takes polypropylene as the matrix, which gives the sheath material certain mechanical strength and chemical resistance; adding ethylene acrylate rubber can enhance the aging resistance of the sheath material to a certain extent.

[0012] Furthermore, the modified glass fiber is prepared by the following steps:

[0013] A1. Add glass fiber into a beaker, then add hydrogen peroxide dropwise, stir and mix evenly, heat to 110°C, reflux for 4 hours, filter, and dry to obtain hydroxylated glass fiber;

[0014] A2. Mix the hydroxylated glass fiber obtained in step A1 with acetone and silane coupling agent KH-172, heat to 80° C., react for 4 hours, filter, and vacuum dry to obtain modified glass fiber.

[0015] Furthermore, the raw materials are calculated in parts by weight as follows: 5-10 parts of glass fiber, 25-45 parts of hydrogen peroxide, 50-70 parts of acetone, and 10-20 parts of silane coupling agent KH-172.

[0016] Glass fiber is a high-strength filling material. The surface of glass fiber is modified by silane coupling agent KH-172 to enhance its surface hydrophobicity, improve the compatibility of glass fiber with polypropylene matrix, make the modified glass fiber dispersed evenly in the matrix, reduce the occurrence of agglomeration, and greatly enhance the mechanical strength of the polypropylene matrix.

[0017] Furthermore, the multi-effect flame retardant is prepared by the following steps:

[0018] S1. Mix 2-methyl-6-tert-butylphenol and potassium hydroxide in a three-necked flask with a thermometer and a reflux device, introduce nitrogen into the device, raise the temperature to 50°C under nitrogen protection, keep warm for 1h, then drop methyl acrylate, and after the addition is complete, quickly raise the temperature to 130°C, react for 4h, and after the reaction is completed, cool to room temperature, add toluene, and adjust the pH to 7 with hydrochloric acid solution, stand to separate the aqueous phase and the organic phase, take the organic phase and distill under reduced pressure to remove toluene, continue to heat, and collect the fraction between 190-210°C as intermediate 1; the ratio of 2-methyl-6-tert-butylphenol, potassium hydroxide and methyl acrylate is 16.4g:0.2g:9.1g;

[0019] Under the catalysis of potassium hydroxide, 2-methyl-6-tert-butylphenol reacts with methyl acrylate to obtain intermediate 1; the specific reaction process is as follows:

[0020]

[0021] S2. At room temperature, under nitrogen protection, add intermediate 1, thiodiethanol, lithium diisopropylamide (catalyst, LAD) and N,N-dimethylformamide (DMF) to a three-necked flask equipped with a stirring device, stir and mix evenly, heat to 80°C, react for 8 hours, and after the reaction is completed, remove the solvent by vacuum distillation, wash with anhydrous ethanol 2-3 times, and obtain intermediate 2; the ratio of intermediate 1, thiodiethanol, lithium diisopropylamide and N,N-dimethylformamide is 24.9g:15.5g:0.5g:100mL;

[0022] Under the catalysis of lithium diisopropylamide, intermediate 1 undergoes an ester exchange reaction with thiodiethanol. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of thiodiethanol, only one hydroxyl group on thiodiethanol participates in the reaction to obtain intermediate 2. The specific reaction process is as follows:

[0023]

[0024] S3, in a three-necked flask equipped with a stirring device, the intermediate 2, sarcosine and toluene were mixed and stirred evenly, and then dibutyltin oxide (catalyst) and dicyclohexylcarbodiimide (DCC, dehydrating agent) were added, and the reaction temperature was controlled to 75°C, and the reaction was kept warm for 6 hours. Stirring was continued during the reaction. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. Then, the mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 1:3), and the eluent was removed by rotary evaporation to obtain intermediate 3; the ratio of the amount of intermediate 2, sarcosine, toluene, dibutyltin oxide and DCC was 33.9 g:8.9 g:150 mL:0.4 g:20.6 g;

[0025] Under the catalysis of dibutyltin oxide and DCC, the hydroxyl group on intermediate 2 and the carboxyl group on sarcosine undergo esterification reaction to obtain intermediate 3. The specific reaction process is as follows:

[0026]

[0027] S4. At room temperature, in a three-necked flask equipped with a stirring device, mix the intermediate 3, N,N-dimethylformamide and N,N-diisopropylethylamine (catalyst) evenly under nitrogen protection, place in an ice bath at 5°C, add ethylene trichlorosilane dropwise, and control the temperature not to exceed 25°C during the addition. After the addition is completed, react at 80°C for 4 hours. After the reaction is completed, distill under reduced pressure, filter, wash with anhydrous ethanol 3-4 times, and vacuum dry to obtain a multi-effect flame retardant; the ratio of the intermediate 3, N,N-dimethylformamide, N,N-diisopropylethylamine, and ethylene trichlorosilane is 123.3g:200mL:30mL:15.9g;

[0028] Under the catalysis of N,N-diisopropylethylamine, intermediate 3 reacts with ethylene trichlorosilane to undergo a nucleophilic substitution reaction. By controlling the molar ratio of the two to be close to 3:1, ethylene trichlorosilane has three chlorine groups participating in the reaction to obtain a multi-effect flame retardant. The specific reaction process is as follows:

[0029]

[0030] The multi-effect flame retardant molecules prepared by the present invention contain Si-N flame retardant components, sulfur elements, semi-hindered phenol structures and carbon-carbon double bonds, wherein the Si-N flame retardant components have the synergistic flame retardant effects of silicon-based and nitrogen-based flame retardants, and compared with general silicon-based flame retardants in which silicon and oxygen are directly connected, Si-N is a covalent bond, and has stable physical and chemical properties, and is not easy to generate SiO2 during combustion, but generates a denser Si-C or Si-Si layer, and has better flame retardant and smoke suppression effects; the introduced sulfur element can accelerate the isomerization of the matrix to produce a large amount of CO2 and catalyze the progress of the Fries rearrangement of the matrix to promote carbonization, and has a synergistic effect with the Si-N flame retardant components to greatly improve the flame retardancy of the matrix; Not only that, the sulfide group can also improve the mechanical properties of the polypropylene matrix; in addition, the introduced semi-hindered phenol antioxidant has an ortho-substituent with an appropriate steric hindrance effect compared with the traditional fully hindered phenol antioxidant. While reducing the bond dissociation energy between the phenolic hydroxyl groups, it also increases the collision probability between the phenolic hydroxyl groups and the system free radicals. It has a higher ability to scavenge free radicals and can enhance the aging resistance of the matrix. The multi-effect flame retardant molecule contains three semi-hindered phenol groups, and its aging resistance is stronger; finally, the introduced carbon-carbon double bond can cross-link with the matrix, which can significantly enhance the migration and exudation resistance of the multi-effect flame retardant, so that the multi-effect flame retardant can perform its performance stably for a long time.

[0031] Beneficial effects of the present invention:

[0032] 1. The sheath material prepared by the present invention is based on polypropylene, which gives the sheath material certain mechanical strength and chemical resistance;

[0033] 2. Adding ethylene acrylate rubber can enhance the aging resistance of the sheath material to a certain extent;

[0034] 3. By modifying the glass fiber, compared with ordinary glass fiber, it has better compatibility with the polypropylene matrix, the agglomeration phenomenon is significantly reduced, and the mechanical strength of the sheath material is enhanced;

[0035] 4. The multi-effect flame retardant prepared can significantly enhance the flame retardancy, aging resistance and mechanical properties of the sheath material to a certain extent, and the performance is long-lasting and stable and not easy to fall off;

[0036] Therefore, the sheath material prepared by the present invention has excellent mechanical strength, stable and efficient flame retardant properties and aging resistance, and has important application value in the field of cable material technology. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Embodiment 1

[0039] Preparation of multi-effect flame retardant:

[0040] S1. In a three-necked flask equipped with a thermometer and a reflux device, 16.4 g of 2-methyl-6-tert-butylphenol and 0.2 g of potassium hydroxide were mixed, nitrogen was introduced into the device, and under the protection of nitrogen, the temperature was raised to 50°C. After keeping the temperature for 1 hour, 9.1 g of methyl acrylate was added dropwise. After the addition was complete, the temperature was quickly raised to 130°C and the reaction was carried out for 4 hours. After the reaction was completed, the temperature was cooled to room temperature, toluene was added, and the pH was adjusted to 7 with a hydrochloric acid solution (mass fraction of 12%). The mixture was allowed to stand to separate the aqueous phase and the organic phase. The toluene was removed by vacuum distillation from the organic phase. The temperature was continued to be raised, and the fraction between 190°C and 210°C was collected as the intermediate 1.

[0041] S2. At room temperature, under nitrogen protection, add 24.9 g of intermediate 1, 15.5 g of thiodiethanol, 0.5 g of lithium diisopropylamide and 100 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirring device. After stirring and mixing evenly, heat to 80°C and react for 8 hours. After the reaction is complete, remove the solvent by vacuum distillation, wash twice with anhydrous ethanol, and obtain intermediate 2;

[0042] S3, in a three-necked flask equipped with a stirring device, 33.9 g of intermediate 2, 8.9 g of sarcosine and 150 mL of toluene were mixed and stirred evenly, and then 0.4 g of dibutyltin oxide and 20.6 g of dicyclohexylcarbodiimide were added, and the reaction temperature was controlled to 75 ° C. The reaction was kept warm for 6 hours, and stirring was continued during the reaction. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 1:3), and the eluent was removed by rotary evaporation to obtain intermediate 3;

[0043] S4. At room temperature and under nitrogen protection, in a three-necked flask equipped with a stirring device, mix 123.3 g of intermediate 3, 200 mL of N,N-dimethylformamide and 30 mL of N,N-diisopropylethylamine evenly, place in an ice bath at 5°C, add 15.9 g of ethylenetrichlorosilane dropwise, and control the temperature not to exceed 25°C during the addition. After the addition is completed, react at 80°C for 4 hours. After the reaction is completed, distill under reduced pressure, filter, wash 3 times with anhydrous ethanol, and dry in vacuo to obtain a multi-effect flame retardant.

[0044] Embodiment 2

[0045] Preparation of multi-effect flame retardant:

[0046] S1. In a three-necked flask equipped with a thermometer and a reflux device, 32.8 g of 2-methyl-6-tert-butylphenol and 0.4 g of potassium hydroxide were mixed, nitrogen was introduced into the device, and under the protection of nitrogen, the temperature was raised to 50°C. After keeping the temperature for 1 hour, 18.2 g of methyl acrylate was added dropwise. After the addition was complete, the temperature was quickly raised to 130°C and the reaction was carried out for 4 hours. After the reaction was completed, the temperature was cooled to room temperature, toluene was added, and the pH was adjusted to 7 with hydrochloric acid solution (mass fraction 12%). The aqueous phase and the organic phase were separated by standing, and the toluene was removed by vacuum distillation of the organic phase. The temperature was continued to be raised, and the fraction between 190-210°C was collected as intermediate 1;

[0047] S2. At room temperature, under nitrogen protection, 49.8 g of intermediate 1, 31 g of thiodiethanol, 1 g of lithium diisopropylamide and 200 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirring device. After stirring and mixing, the mixture was heated to 80°C and reacted for 8 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was washed twice with anhydrous ethanol to obtain intermediate 2.

[0048] S3, in a three-necked flask equipped with a stirring device, 67.8g of intermediate 2, 17.8g of sarcosine and 300mL of toluene were mixed and stirred evenly, and then 0.8g of dibutyltin oxide and 41.2g of dicyclohexylcarbodiimide were added, and the reaction temperature was controlled to 75°C, and the reaction was kept warm for 6h. Stirring was continued during the reaction. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 1:3), and the eluent was removed by rotary evaporation to obtain intermediate 3;

[0049] S4. At room temperature and under nitrogen protection, in a three-necked flask equipped with a stirring device, mix 246.6 g of intermediate 3, 400 mL of N,N-dimethylformamide and 60 mL of N,N-diisopropylethylamine evenly, place in an ice bath at 5°C, add 31.8 g of ethylenetrichlorosilane dropwise, and control the temperature not to exceed 25°C during the addition. After the addition is completed, react at 80°C for 4 hours. After the reaction is completed, distill under reduced pressure, filter, wash 3 times with anhydrous ethanol, and dry in vacuo to obtain a multi-effect flame retardant.

[0050] Embodiment 3

[0051] Preparation of modified glass fiber:

[0052] A1. Add 5 g of glass fiber into a beaker, then add 25 g of hydrogen peroxide dropwise, stir and mix evenly, heat to 110°C, reflux for 4 hours, filter, and dry to obtain hydroxylated glass fiber;

[0053] A2. Mix the hydroxylated glass fiber obtained in step A1 with 50 g of acetone and 10 g of silane coupling agent KH-172, heat to 80° C., react for 4 hours, filter, and vacuum dry to obtain modified glass fiber.

[0054] Embodiment 4

[0055] Preparation of modified glass fiber:

[0056] A1. Add 10 g of glass fiber into a beaker, then add 45 g of hydrogen peroxide dropwise, stir and mix evenly, heat to 110°C, reflux for 4 hours, filter, and dry to obtain hydroxylated glass fiber;

[0057] A2. Mix the hydroxylated glass fiber obtained in step A1 with 70 g of acetone and 20 g of silane coupling agent KH-172, heat to 80° C., react for 4 hours, filter, and vacuum dry to obtain modified glass fiber.

[0058] Embodiment 5

[0059] 80g of polypropylene resin was placed in a vacuum oven and dried at 100°C for 12h. The fully dried polypropylene resin, 20g of ethylene acrylate rubber, 5g of the multi-effect flame retardant prepared in Example 1, 10g of the modified glass fiber prepared in Example 3, 0.1g of benzoyl peroxide and 2g of paraffin were put into a blender and mixed for 30min. The mixture was then added into a twin-screw extruder, melt-blended and extruded to obtain a copper wire sheath material.

[0060] Embodiment 6

[0061] 90 g of polypropylene resin was placed in a vacuum oven and dried at 100° C. for 12 h. The fully dried polypropylene resin, 25 g of ethylene acrylate rubber, 10 g of the multi-effect flame retardant prepared in Example 2, 15 g of the modified glass fiber prepared in Example 4, 0.2 g of tert-butyl perbenzoate and 3 g of stearyl zinc were put into a blender and mixed for 30 min. The mixture was then added into a twin-screw extruder, melt blended and extruded to obtain a copper wire sheath material.

[0062] Embodiment 7

[0063] 100 g of polypropylene resin was placed in a vacuum oven and dried at 100° C. for 12 h. The fully dried polypropylene resin, 30 g of ethylene acrylate rubber, 15 g of the multi-effect flame retardant prepared in Example 2, 20 g of the modified glass fiber prepared in Example 4, 0.3 g of tert-butyl perbenzoate and 4 g of stearyl zinc were put into a blender and mixed for 30 min. The mixture was then added into a twin-screw extruder, melt-blended and extruded to obtain a copper wire sheath material.

[0064] Comparative Example 1

[0065] A commercially available nitrogen-based flame retardant of equal quality was used to replace the multi-effect flame retardant in Example 7, and the remaining steps were the same as those in Example 7 to obtain a sheath material.

[0066] Comparative Example 2

[0067] Commercially available polypropylene sheath material was used.

[0068] Embodiments 5, 6, 7, and comparative examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:

[0069] The tensile properties are determined using the national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics";

[0070] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to measure the limiting oxygen index before and after 180 days of storage at room temperature;

[0071] The oxidation induction time was determined using the national standard GB / T 19466.6-2009 "Plastics Differential Scanning Calorimetry (DSC) Part 6: Determination of Oxidation Induction Time (Isothermal OIT) and Oxidation Induction Temperature (Dynamic OIT)";

[0072] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 30 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2, determine the tensile strength after aging (GB / T1040.2-2006), and calculate the tensile strength retention rate; tensile strength retention rate = tensile strength after test / tensile strength before test × 100%;

[0073] The measured results are shown in the following table:

[0074]

[0075] It can be seen from the above table that the mechanical strength, flame retardant properties and aging resistance of the sheath material prepared in the embodiments of the present invention are higher than those of the control example, and the performance is long-lasting and stable; in addition, with the increase of the content of the multi-effect flame retardant in embodiments five to seven, the flame retardant properties and aging resistance of the sheath material are significantly improved, so the present invention has important application value in the field of cable material technology.

[0076] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0077] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a copper wire sheath material, characterized in that: Prepared by the following steps: The polypropylene resin is dried, and the fully dried polypropylene resin is mixed with ethylene acrylate rubber, multi-effect flame retardant, modified glass fiber, initiator and lubricant in a mixer, and then added into a twin-screw extruder, melt-blended and extruded to obtain a copper wire sheath material.

2. The method for preparing a copper wire sheath material according to claim 1, characterized in that: The multi-effect flame retardant is prepared by the following steps: S1. Mix 2-methyl-6-tert-butylphenol and potassium hydroxide, raise the temperature to 50°C under nitrogen protection, keep warm for 1 hour, then drop methyl acrylate, and after the addition is complete, quickly raise the temperature to 130°C, react for 4 hours, and after the reaction is completed, cool to room temperature, add toluene, adjust pH to 7, stand to separate the aqueous phase and the organic phase, take the organic phase and distill under reduced pressure, continue to raise the temperature, and collect the fraction between 190-210°C, which is intermediate 1; S2. At room temperature, under nitrogen protection, add intermediate 1, dithiodiethanol, lithium diisopropylamide and N,N-dimethylformamide into a three-necked flask equipped with a stirring device, stir and mix evenly, then heat to 80°C and react for 8h. After the reaction is complete, distill under reduced pressure and wash to obtain intermediate 2; S3, mixing intermediate 2, sarcosine and toluene, stirring evenly, then adding dibutyltin oxide and dicyclohexylcarbodiimide, and reacting at 75°C for 6 hours, stirring continuously during the reaction, filtering, rotary evaporation, column chromatography purification, and rotary evaporation to obtain intermediate 3; S4. At room temperature and under nitrogen protection, mix the intermediate 3, N,N-dimethylformamide and N,N-diisopropylethylamine evenly, place in an ice bath at 5°C, add ethylenetrichlorosilane dropwise, and control the temperature not to exceed 25°C during the addition. After the addition is completed, react at 80°C for 4h. After the reaction is completed, distill under reduced pressure, filter, wash and dry in vacuo to obtain a multi-effect flame retardant.

3. The method for preparing a copper wire sheath material according to claim 2, characterized in that: In step S1, the ratio of 2-methyl-6-tert-butylphenol, potassium hydroxide and methyl acrylate is 16.4 g:0.2 g:9.1 g.

4. The method for preparing a copper wire sheath material according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, thiodiethanol, lithium diisopropylamide, and N,N-dimethylformamide is 24.9 g:15.5 g:0.5 g:100 mL.

5. The method for preparing a copper wire sheath material according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 2, sarcosine, toluene, dibutyltin oxide and DCC is 33.9 g:8.9 g:150 mL:0.4 g:20.6 g.

6. The method for preparing a copper wire sheath material according to claim 2, characterized in that: In step S4, the ratio of the amount of intermediate 3, N,N-dimethylformamide, N,N-diisopropylethylamine, and ethylenetrichlorosilane is 123.3 g: 200 mL: 30 mL: 15.9 g.

7. The method for preparing a copper wire sheath material according to claim 1, characterized in that: The modified glass fiber is prepared by the following steps: A1. Add glass fiber into a beaker, then add hydrogen peroxide dropwise, stir and mix evenly, heat to 110°C, reflux for 4 hours, filter, and dry to obtain hydroxylated glass fiber; A2. Mix the hydroxylated glass fiber obtained in step A1 with acetone and silane coupling agent KH-172, react at 80° C. for 4 hours, filter, and vacuum dry to obtain modified glass fiber.

8. The method for preparing a copper wire sheath material according to claim 7, characterized in that: The raw materials are calculated in parts by weight as follows: 5-10 parts of glass fiber, 25-45 parts of hydrogen peroxide, 50-70 parts of acetone, and 10-20 parts of silane coupling agent KH-172.

9. The method for preparing a copper wire sheath material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 80-100 parts of polypropylene resin, 20-30 parts of ethylene acrylate rubber, 5-15 parts of multi-effect flame retardant, 10-20 parts of modified glass fiber, 0.1-0.3 parts of initiator, and 2-4 parts of lubricant.

10. A copper wire sheath material, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Composite copper foil and preparation method thereof

    CN120554789A